Cross-Reactive Antibodies in Tick-Borne Encephalitis: Case Report and Literature Review - Tatjana Vilibic-Cavlek; Thomas Ferenc; Mateja Vujica Ferenc; Maja Bogdanic; Tanja Potocnik-Hunjadi; Dario Sabadi; Vladimir Savic; Ljubo Barbic; Vladimir Stevanovic; Federica Monaco; Eddy Listes; Giovanni Savini (Antibodies, 2022)
Flaviviruses are a heterogeneous group of viruses that may induce broad antigenic cross-reactivity. We present a patient who was admitted to the infectious disease department with symptoms suggestive of aseptic meningitis. During the clinical workup, the patient reported a tick bite two weeks before the disease onset. High titers of IgM and IgG antibodies to tick-borne encephalitis virus (TBEV) were found in both serum and cerebrospinal fluid (CSF) samples, indicating acute TBEV infection. West Nile virus (WNV) and Usutu virus (USUV) IgM and/or IgG antibodies were also detected, and a virus neutralization test (VNT) was performed. A high titer of TBEV neutralizing (NT) antibodies (640) was detected, which confirmed acute TBE. However, NT antibodies to WNV and USUV were also detected (titer 80 for both viruses). After TBEV and WNV IgG avidity evaluation, previous flavivirus infection was highly suspected (avidity index 82% and 89%, respectively). Blood, CSF, and urine samples were negative for respective viruses’ RNA. The presented case highlights the challenges in flavivirus serodiagnosis. In the published literature, different degrees of cross-reactivity or cross-neutralization between TBEV and dengue, louping ill, Omsk hemorrhagic fever, Langat, and Powassan virus were also observed. Therefore, the serology results should be interpreted with caution, including the possibility of cross-reactivity. In areas where several flaviviruses co-circulate VNT is recommended for disease confirmation.